A new era of transformation in Ghana: Lessons from the past and scenarios for the future - Breisinger, Clemens; Diao, Xinshen; Kolavalli, Shashidhara; Al Hassan, Ramatu M.; Thurlow, James (International Food Policy Research Institute, 2011)
Several Sub-Saharan African nations have experienced increased economic growth and political stability in recent years compared with the stagnation and turmoil of previous decades. Ghana is one of the biggest success stories of the region; the nation has enjoyed an annual average of five percent economic growth for the past 20 years and will probably be the first Sub-Saharan African country to achieve the Millennium Development Goal of cutting poverty in half by 2015.